2007
DOI: 10.1038/sj.eye.6702755
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Microscopy Coil MR-Eye

Abstract: The eye is involved in several pathologies where precise identification of the underlying condition is essential for the optimal patient care. This preliminary report presents the potential of high-resolution microscopy coil magnetic resonance imaging (HR-MRI) to undertake this task being actively used in the clinical setting. We used a commercially available MRI scanner and a microscopy surface coil. Exquisite anatomic detail of the eye and orbit with depiction of previously unobserved structures and clear de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 6 publications
0
26
0
2
Order By: Relevance
“…Recent advances in MR imaging make it possible to more closely examine the interface between anatomic disruption and physiologic dysfunction. 36 [40][41][42][43][44] fMRI has been used in mapping the function of cortical regions in a variety of healthy and disease states involving vision. 45,46 In cases involving papilledema, fMRI of the visual pathway and particularly the retina may offer insight into the effect of papilledema on visual impairment.…”
Section: Future Directions Of Mr Imaging In Papilledema Imagingmentioning
confidence: 99%
“…Recent advances in MR imaging make it possible to more closely examine the interface between anatomic disruption and physiologic dysfunction. 36 [40][41][42][43][44] fMRI has been used in mapping the function of cortical regions in a variety of healthy and disease states involving vision. 45,46 In cases involving papilledema, fMRI of the visual pathway and particularly the retina may offer insight into the effect of papilledema on visual impairment.…”
Section: Future Directions Of Mr Imaging In Papilledema Imagingmentioning
confidence: 99%
“…3.5 min) was developed. The scan sequences yield a voxel volume of 0.004 mm 3 and an ineplane resolution 0.08 mm 2 significantly better as compared with other studies using 1.5T systems [5,14,28,30,32,33] and comparable even with higher field systems (3e7T) [6,12,22,29].…”
Section: Discussionmentioning
confidence: 90%
“…Particularly, T1-weighted (T1w) images can provide better anatomical detail but the strong orbital fat signal can over-saturate smaller adjacent structures [5,6,29,31]. T2-weighting can improve visualization of the inner surface of the globe, because of the bright vitreous signal, but is vulnerable to motion artifacts, H 0 artifacts and has lower SNR [22,31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The use of small coils is recommended for ocular MR imaging. 9 A head coil can also be used to examine orbital content and has been found useful for comparing structures in the 2 orbits. 10,11 Previous studies indicated that use of the appropriate coil is decisive in the success of orbital MR imaging.…”
Section: Introductionmentioning
confidence: 99%